2001
DOI: 10.1074/jbc.m008260200
|View full text |Cite
|
Sign up to set email alerts
|

Glutathiolation of Proteins by Glutathione DisulfideS-Oxide Derived from S-Nitrosoglutathione

Abstract: S-Nitrosoglutathione (GSNO) undergoes spontaneous degradation that generates several nitrogen-containing compounds and oxidized glutathione derivatives. We identified glutathione sulfonic acid, glutathione disulfide S-oxide (GS(O)SG), glutathione disulfide S-dioxide, and GSSG as the major decomposition products of GSNO. Each of these compounds and GSNO were tested for their efficacies to modify rat brain neurogranin/RC3 (Ng) and neuromodulin/GAP-43 (Nm). Among them, GS(O)SG was found to be the most potent in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 39 publications
6
69
0
Order By: Relevance
“…With NEMmodified peptides taken into account, ϳ90% of the unacylated Cys residues exist as free sulfhydryl groups in vivo, presumably due to the high concentration of reduced glutathione. The availability of free sulfhydryl groups on cysteines 3 and 4 allows GAP-43 to be additionally modified by ADP-ribosylation (31) and glutathiolation by glutathione disulfide S-oxide (32).…”
Section: Discussionmentioning
confidence: 99%
“…With NEMmodified peptides taken into account, ϳ90% of the unacylated Cys residues exist as free sulfhydryl groups in vivo, presumably due to the high concentration of reduced glutathione. The availability of free sulfhydryl groups on cysteines 3 and 4 allows GAP-43 to be additionally modified by ADP-ribosylation (31) and glutathiolation by glutathione disulfide S-oxide (32).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that S-thiolation occurs at the reactive and catalytically essential cysteine 149 (34). Oxidation of this residue inactivates the enzyme and may be achieved by a range of oxidants including GSSG, GSNO, NO, HOCl, and GS(O)SG (33,(35)(36)(37)(38)(39)(40). Triosephosphate isomerase is another glycolytic enzyme that we found to be S-thiolated during cardiac oxidative stress.…”
Section: S-thiolation During Cardiac Oxidant Stress and Functionalmentioning
confidence: 99%
“…Previously, we showed that treatment of rat brain slices with oxidants could generate reactive oxidized glutathione derivatives, GS-DSMO and GS-DSDO, which caused protein glutathionylation and formation of protein disulfide (29). Incubation of the purified CaMKII with GS-DSMO at 0.1 (Fig.…”
Section: Oxidative Modification Of Camkii In Mouse Brainmentioning
confidence: 99%
“…It is conceivable that these reactive oxygen species could modulate CaMKII activity by direct oxidation of this protein, which constitutes 1-2% of total brain protein (27), as well as by oxidation of its activator, CaM (28). Previously, we showed that activation of NMDA receptors or direct administration of oxidants to the brain slices could trigger thionylation of neurogranin and formation of intra-molecular disulfide of this protein (29,30). The oxidant-induced modification of protein was hypothesized as a result of oxidation by the endogenously produced glutathione disulfide S-oxides (GS-DSOs), which have a high activity to form glutathione-protein-mixed disulfide (glutathionylation) and inter-and/or intra-molecular disulfide bonds of proteins (31)(32)(33).…”
mentioning
confidence: 99%